Fields and the Intelligibility of Contact Action. (21st April 2015) - Sherry, David
Abstract: This article concerns arguments for the impossibility of contact action and, subsequently, the use of force fields to render intelligible apparent cases of contact action. I argue that instead of unraveling the mystery of contact action, fields only deepen the mystery. Further, I show that there is a confusion underlying arguments for the impossibility of contact and present an analysis of contact, based upon Körner's treatment of empirical continuity, which restores intelligibility to apparent cases of contact action.